Natural chondroitin sulphates increase aggregation of proteoglycan complexes and decrease adamts-5 expression in interleukin 1β-treated chondrocytes. Issue 5 (27th September 2007) - Tahiri, K; Korwin-Zmijowska, C; Richette, P; Héraud, F; Chevalier, X; Savouret, J-F; Corvol, M-T
Abstract : Objective: To assess the effect of natural chondroitin sulphate (CS) on the ability of neosynthesised sulphated proteoglycans (PGs) to aggregate in cultured chondrocytes treated with interleukin (IL)1β. Methods: Primary cultured rabbit articular chondrocytes were treated or not with IL1β alone or with concentrations of CS for 20 h. Neosynthesised PGs were labelled by incorporation of [35 SO4 ]-sulphate and analysed by chromatography on Sepharose 2B columns. Gelatinolytic activity was measured by zymography, and matrix metalloproteinase (MMP)1 mRNA level in chondrocytes underwent real-time PCR. Expression of ADAMTS (for "a disintegrin and metalloproteinase with thrombospondin motifs") -4 and -5 was analysed by real-time PCR and western blotting. Results: The production of [35 SO4 ]-labelled PGs was significantly increased with 10 μg/ml CS in the cellular pool rather than in the incubation medium. The addition of CS to IL1β-treated cells inhibited in part the disaggregation of sulphated PGs induced by IL1β. This inhibitory effect of CS is associated with a significant decrease in ADAMTS-5 expression at the mRNA and protein levels. No effect of CS was observed on IL1β-induced gelatinolytic activity, MMP1 mRNA expression or ADAMTS-4 expression. Conclusion: CS increases the production of functional sulphated PGs in the direct environment of chondrocytes in vitro. This beneficial effect of CS in IL1β-treated cells is associated with decreased expression of ADAMTS-5.